(untitled) (International Journal of Engineering and Computer Science, 2014)
Using Wi-Fi at homes, offices, colleges will now become a thing of the past. Now we have Li-fi, Light Fidelity, refers to wireless communication systems using light from light emitting diodes as a medium instead of traditional radio frequencies, as in Wi-Fi. Li-fi is expected to be ten times cheaper than wi-fi. Li-Fi has the advantage of being able to be used in electromagnetic sensitive areas such as in aircraft or nuclear power plants, without causing interference. However, the light waves cannot penetrate walls which makes Li-Fi more secure relative to Wi-Fi. The visible light spectrum is 10,000 times larger than the entire radiofrequency spectrum. This paper will focus on Li-Fi technology over Wi-Fi technology and challenges for the new VLC technology.